An analysis of dental arch form and arch dimensions of the Nepalese adults aged 17-32 years - Rabindra, Man Shrestha
Dental arch forms and dimensions vary between the sexes and among the racial groups. Also, human dental arch acquires a stable form and dimension with the attainment of adulthood. These statements signify the need for the predetermination of arch forms and mean arch dimensions applicable to a particular adult population to harmonize with the natural pattern. This can subsequently be applied on diagnosis and treatment planning of orthodontic patients. The purpose of the present study is threefold: first, to analyze the Nepalese dental arch forms and to classify them into morphological types; second, to determine the mean arch dimensions; and third, to establish the Bolton's overall ratio and anterior ratio for the Nepalese adults. Dental stone models of one hundred Nepalese adults aged 17-32 years with excellent occlusion, dentofacial proportion and acceptable facial profile were studies using standardized Boley gauze (0.1 mm accuracy). The study compared gender differences and bilateral variations of arch dimensions among the Nepalese population as well as between the Nepalese and Caucasian samples. Arch form analysis was done using Raberin's mathematical method of sixth degree polynomial. The results showed the distribution of the Nepalese arch form types as : 26% flat arch, 24% wide arch, 19% pointed arch, 18% narrow arch and 13% mid arch. Male samples possessed the predominance of wide dental arches (36%) while females possessed the predominance of flat arches (30%). Arch dimensions of the Nepalese males were significantly greater than those of the females for many of the parameters studies (P < 0.05). The study showed arch asymmetry for some of the parameters of arch dimensions. The mean mesio-distal crown diameters of the Nepalese were lesser than those of the Caucasian subjects. The maxillary arch widths of the Nepalese adults were significantly lesser than the Caucasians according to the measurement method of Lavelle. However, maxillary arch widths were greater in Nepalese samples when measured using Burris' method. Arch depths at molars were significantly lesser in both Nepalese females and males when compared to the Caucasian counterparts (P < 0.05). Arch lengths of the Nepalese adults were significantly greater than the Caucasians at most of the reference points. The Bolton's overall ratio for the Nepalese adults was found to be 91.08 (SD 1.80) and the anterior ratio was found to be 76.68 (SD 2.21). The difference between the mean Bolton ratios between the Nepalese females and males, as well as between the Nepalese and Caucasian subjects were not statistically significant (P > 0.05). The result presents a clinical applicability in using the Bolton's ratios universally.
Vita.
Thesis (Master of Science in Dentistry) -- University of the Philippines, Manila
Keywords: Dental arch -- Growth and development; Orthodontics